Legal Discourse of United States Pharmaceutical Industry Mandatory License and Trips Agreement Post Doha Declaration - Wahyu Pratama Aji (Activa Yuris: Jurnal Hukum, 2022)
The public health crisis related to HIV/AIDS, Tuberculosis and Malaria, was the starting point for the World Trade Organization (WTO) Ministerial Conference in 2001 which adopted the Doha Declaration on the TRIPS (Trade-Related Aspects of Intellectual Property Rights) and Public Health Agreements. The pharmaceutical industry as one of the knowledge driven sectors especially pharmaceutical research is very expensive and unpredictable. Making the patent system as a legal protection tool to facilitate innovation related to pharmaceutical products. The similarities between United States patent law and the TRIPS agreement also demonstrate United States’s influence in setting intellectual property standards globally. This research is a juridical-normative research using a statutory approach. The data collection technique was carried out by means of a literature study. Data analysis technique: qualitative normative analysis. The results showed that the United States' dissatisfaction with the level of intellectual property protection provided by the TRIPS agreement encouraged the development of the provisions of the TRIPS-Plus agreement in the United States Free Trade Area (FTA). The terms of the TRIPS-Plus agreement appear to be designed to negate the effective use of mandatory licensing by blocking the marketing of third-party drugs during the term of the patent. However, the TRIPS agreement retains some flexibility for World Trade Organization members, such as the data exclusivity and mandatory licensing outlined in the Doha Declaration.